Impatiens glabrata (Balsaminaceae)—A new species from southern Western Ghats, India - Prabhukumar, K.m.; Hareesh, V.s.; Bhaskar, V.; Sreekumar, V.b.; Nirmesh, T.k.; Balachandran, Indira (Phytotaxa, 2016)
Impatiens glabrata, a new species, is described from Muthikulam forest of Palakkad district, Kerala, India. A description and observations on pollen morphology, ecology, distribution and its allied characters between I. henslowiana and I. fruticosa are provided, along with colour photographs.